2020
DOI: 10.1186/s12931-020-01477-y
|View full text |Cite
|
Sign up to set email alerts
|

FGL1 regulates acquired resistance to Gefitinib by inhibiting apoptosis in non-small cell lung cancer

Abstract: Background: This study investigated the role of fibrinogen-like protein 1 (FGL1) in regulating gefitinib resistance of PC9/GR non-small cell lung cancer (NSCLC). Methods: The effect of different concentrations of gefitinib on cell proliferation were evaluated using the CCK-8 assay. FGL1 expression in the normal human bronchial epithelial cell line Beas-2B, as well as four lung tumor cell lines, H1975, A549, PC9, and PC9/GR, was investigated by using western blotting and qRT-PCR. FGL1 was knocked down using sma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…Further, Bie et al reported, via through TCGA and GEO database data mining and in vitro functional experiments, that the loss of FGL1 promotes cell growth, epithelial-mesenchymal transition (EMT), and angiogenesis in LKB1-mutant lung adenocarcinoma [ 24 ]. However, Sun et al reported that FGL1 confers gefitinib resistance and that the knockdown of FGL1 in lung adenocarcinoma cells induces antitumor effects in vivo [ 36 ]. Therefore, further preclinical and clinical studies of HCC are necessary to clarify the role of FGL1 and its impact on HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Bie et al reported, via through TCGA and GEO database data mining and in vitro functional experiments, that the loss of FGL1 promotes cell growth, epithelial-mesenchymal transition (EMT), and angiogenesis in LKB1-mutant lung adenocarcinoma [ 24 ]. However, Sun et al reported that FGL1 confers gefitinib resistance and that the knockdown of FGL1 in lung adenocarcinoma cells induces antitumor effects in vivo [ 36 ]. Therefore, further preclinical and clinical studies of HCC are necessary to clarify the role of FGL1 and its impact on HCC.…”
Section: Discussionmentioning
confidence: 99%
“…FGL1 induces insulin resistance through an ERK1/2-dependent pathway in hepatocytes, and induces adipogenesis by stimulating the ERK1/2-C/EBPβ-dependent pathway 16 . Some non-small cell lung cancer (NSCLC) patients are acquired resistance to gefitinib, a drug for NSCLC therapy, Sun et al found that FGL1 was upregulated in gefitinib-resistant cancer cells, and mediated the resistance to gefitinib in NSCLC cells by regulating the PARP1/ Caspase 3 pathway 57 . Lymphocyte activation gene 3 (LAG-3) is a transmembrane protein that is generally expressed on the surface of activated immune cells, such as NK cells, T cells, and other immune cells 58 .…”
Section: Fgl1 and Fgl2 Signaling Pathwaysmentioning
confidence: 99%
“…Meanwhile, FGL1 accelerates the proliferation, migration, and invasion of GC cells, accordingly FGL1 can be used as a target for the treatment of GC and a predictor of the prognosis of GC patients 12 . Gefitinib resistance can be regulated by FGL1 through inhibiting the apoptosis of the non-small cell lung cancer (NSCLC) cell line PC9/GR, and FGL1 can act as a latent therapeutic target for NSCLC 57 . Besides, Chen et al have conducted in-depth studies on the role of FGL1 that they inoculated MC38 (a type of colon cancer cell) through mice and found that the tumor growth of FGL1-KO mice was significantly slower than that of WT mice 15 .…”
Section: The Role Of Fgl1 and Fgl2 In Tumorsmentioning
confidence: 99%
“…It has been reported that FGL1 confers gefitinib resistance in the NSCLC cell line PC9/GR by regulating the PARP1/caspase 3 pathway. Hence, FGL1 maybe a potential therapeutic target to improve the treatment response of NSCLC patients with acquired resistance to gefitinib (11). Also, It is found that the plasma FGL1 concentrations were significantly higher in the obese group than those in the normal weight group and FGL1 may induce adipogenesis through an ERK1/2-C/EBPb-dependent pathway in 3T3-L1 adipocytes.…”
Section: Introductionmentioning
confidence: 91%